2016
DOI: 10.9767/bcrec.11.2.443.250-261
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamics of Methylene Blue Adsorption onto Zero Valent Iron Supported on Mesoporous Silica

Abstract: Zero valent iron supported on mesoporous silicanano particles (NZVI/MSNs) was prepared by the aqueous phase borohydride reduction methods. Prior to the reduction, mesoporous silica nanoparticles (MSNs) were prepared through the activation of fumed silica with concentrated HCl by refluxing at 90 °C. FTIR, XRD, FESEM, EDX and BET were used to characterize theadsorbents prepared. BET surface areas of MSNs, NZVI, and NZVI/MSNs were 126, 41, and 72 m 2 /g for, respectively. The performance of NZVI/MSNs as adsorbent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As seen from Table 3, with the pseudo-second-order and pseudo-first-order models, that were used to test the adsorption kinetically, the pseudo-second-order models showed the better fit of the empirical data with R 2 from 0.98 to 0.99. 21,22 , the change of enthalpy (∆H°) for both synthetic dyes in this study was negative or exothermic as shown on the less in adsorption percentage with increases in temperature. The positive values of entropy change (∆S°) for both synthetic dyes maintain the elevated randomness at the solution -solid interface along with the adsorption of the dye on the surface of silica.…”
mentioning
confidence: 49%
“…As seen from Table 3, with the pseudo-second-order and pseudo-first-order models, that were used to test the adsorption kinetically, the pseudo-second-order models showed the better fit of the empirical data with R 2 from 0.98 to 0.99. 21,22 , the change of enthalpy (∆H°) for both synthetic dyes in this study was negative or exothermic as shown on the less in adsorption percentage with increases in temperature. The positive values of entropy change (∆S°) for both synthetic dyes maintain the elevated randomness at the solution -solid interface along with the adsorption of the dye on the surface of silica.…”
mentioning
confidence: 49%
“…The adsorption of cationic dye MB particularly takes place at acidic pH, where the oxide/hydroxide surface becomes negatively charged and can form surface complexes with cations. The complexes of MB and intermediates with iron(II) and iron(III) oxides/hydroxides are also adsorbed on the nZVI surface .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the maximum removal of 50 (mg⋅L −1 ) MB could be achieved within 60 min with zero‐valent iron supporting mesoporous silica (NZVI/MSNS). NZVI/MSNS exhibits good performance in the adsorption of methylene blue with an adsorption capacity of 71 (mg⋅L −1 ), and it can be considered as a promising adsorbent for application in industrial waste water remediation .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the system requires a net energy for effective adsorption that provides an endothermic process. On the basis of the obtained thermodynamic parameters, the adsorption process was concluded to be both endothermic and spontaneous (Hameed et. al.…”
Section: Adsorption Thermodynamicsmentioning
confidence: 99%